P96 A New Interactive Game Device May Improve Compliance With Spacer Devices In Very Young Children. (10th November 2014) - Murray, CS; Shakir, S; Aslam, T
Abstract : Background: The use of spacers in young children is not always easy and can result in distressed children and parents. We aimed to develop and assess an interactive electronic game to improve ease of use and potentially compliance with inhalers in young children. Methods: The Respiratory Aid For Inhalers (RAFIhaler) consists of an electronic sensor adjacent to the outflow valve of a spacer mask, providing input every 0.1 seconds to a custom designed android application on a smartphone that is mounted, in full view of the child, on top of the spacer. The application displays on-screen characters designed to respond to correct breathing as part of a game storyline, for example by blowing away characters unfriendly to the hero (RAFI) or blowing his boat across a river. The RAFIhaler was developed through iterative testing and multiple redesigns of hardware and software until a satisfactory final module was completed. This module was tested on 14 children admitted to hospital with acute wheeze by an independent researcher, along with a survey to assess the child's reaction and the parent and child's perceived benefit from RAFIhaler. Open-ended questions allowed further feedback. Results: Fourteen children (2–7 yrs, 7M:7F) participated; 13 children and 14 parents completed the survey. All children stated they enjoyed the activity. Eleven children responded further; 10(91%) felt the RAFIhaler helped them taking medication. All but one parent felt that RAFIhaler helped their child use the spacer. Of the thirteen parents who felt the RAFIhaler helped, three felt their child previously really struggled with the inhaler. Some benefits of RAFIhaler voiced by parents were: enjoyable (3); good distraction (3); made child calmer (2); helped in breathing/inhalation technique (3); would be useful at home (1). One parent felt RAFIhaler was not of benefit as they felt their child already took their inhaler well. Conclusions: Children universally found using the RAFIhaler with their spacer enjoyable. The majority of parents felt the RAFIhaler helped their child take their medicine. The RAFIhaler may be of use both in encouraging young children to use their inhaler/spacer, and in combatting anxiety and stress associated with their use.